FINANCIAL INDICATORS AND ADDED ECONOMIC VALUE IN VALUE CREATION - Vergiú Canto, Jorge (2007)
An enterprise aim is to search the increasing of an enterprise's value through maximizing utilities and heritage with the purpose of minimizing risk levels and thus to obtain a suitable solvency in order to face short-time engagements. The real challenge to find the enterprise's value and to interpret it, through Financial Indicators that, even though they are considered to be clear and easy reasons to be worked out, might decrease their effectiveness as instruments for wealth measuring and the Added Economic Value(AEV) which is a tool which tries to counteract these indicators limitations by valueing and assessing any management perfomance through value creation.